Honey as an antioxidant therapy to reduce cognitive ageing - Azman, Khairunnuur Fairuz (Iran J Basic Med Sci, 2019)
This paper reviews the potential role of honey as a therapeutic antioxidant to reduce oxidative stress and improve cognitive ageing. All articles indexed to PubMed Central (PMC) were searched using the following key words: honey, antioxidant, memory and ageing. Honey is a natural insect-derived product with therapeutic, medicinal and nutritional values. Antioxidant properties of honey quench biologically-circulating reactive oxygen species (ROS) and counter oxidative stress while restoring the cellular antioxidant defense system. Antioxidant properties of honey may complement its nootropic effects to reduce cognitive ageing.